Jejunal graft conduits after esophagectomy - Gaur, Puja; Blackmon, Shanda H. (Journal of Thoracic Disease, 2014)
Introduction: The jejunum is uniquely suitable for esophageal reconstruction because it is relatively abundant, does not require a formal preparation, is typically free of disease, has similar luminal size compared to the esophagus, has intrinsic peristalsis, and may not undergo senescent lengthening to the extent that colon does. Methods: To obtain data to determine the outcomes of jejunal interposition for esophageal replacement, electronic databases were searched, including MEDLINE (Ovid SP), Scopus, EMBASE (Ovid SP), Science Direct’s full-text database, and the Cochrane Library from January 1990 to September 2013. Results: Two-hundred and forty-six abstracts were reviewed and an article search was performed on selected abstracts. Additional references from article bibliographies were included as appropriate. A thorough search of the literature demonstrates the widespread use of jejunum, either as a free, pedicled, or free- and pedicled-graft with acceptable results. Conclusions: Any region of the esophagus can be replaced by jejunum, whether it is distal esophagus as a Merendino procedure for a vagal-sparing esophagectomy and segmental jejunal reconstruction connected to stomach, mid-thoracic esophagus as a pedicled jejunal interposition or free flap, cervical esophagus as a free segmental interposition, or the entire length as a long-segment super-charged pedicled jejunal interposition. When used, the jejunum is either pedicled, augmented ("super-charged"), a free segment (requiring microvascular anastomosis of artery and vein), or a combination of the above.